2013
DOI: 10.1021/bi4012644
|View full text |Cite
|
Sign up to set email alerts
|

Role of Active Site Residues in Promoting Cobalt–Carbon Bond Homolysis in Adenosylcobalamin-Dependent Mutases Revealed through Experiment and Computation

Abstract: Adenosylcobalamin serves as a source of reactive free radicals that are generated by homolytic scission of the coenzyme’s cobalt-carbon bond. AdoCbl-dependent enzymes accelerate AdoCbl homolysis by ~1012-fold, but the mechanism by which this is accomplished remains unclear. We have combined experimental and computational approaches to gain molecular-level insight into this process for glutamate mutase. Two residues, glutamate-330 and lysine-326, form hydrogen bonds with the adenosyl group of the coenzyme. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…Other AdoCbl-dependent mutases similarly position their substrates at the same distance from the Cbl, as determined from crystal structures (24,29,33) and by electron paramagnetic resonance spectroscopic studies of glutamate mutase (62) and MCM (63) under catalytic conditions. Pseudorotation of the 5Ј-dAdo ribose has also been suggested from structural and biochemical studies of glutamate mutase (33,55) and from computational studies on MCM (64). Thus, given the combined structural, biochemical, and computational evidence, it appears that this mechanism of moving the active C5Ј radical toward substrate is conserved in AdoCbl-dependent mutases such as acyl-CoA mutases.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other AdoCbl-dependent mutases similarly position their substrates at the same distance from the Cbl, as determined from crystal structures (24,29,33) and by electron paramagnetic resonance spectroscopic studies of glutamate mutase (62) and MCM (63) under catalytic conditions. Pseudorotation of the 5Ј-dAdo ribose has also been suggested from structural and biochemical studies of glutamate mutase (33,55) and from computational studies on MCM (64). Thus, given the combined structural, biochemical, and computational evidence, it appears that this mechanism of moving the active C5Ј radical toward substrate is conserved in AdoCbl-dependent mutases such as acyl-CoA mutases.…”
Section: Discussionmentioning
confidence: 93%
“…To accelerate Co-C bond homolysis, substrate binding likely modulates the interactions between the protein and the 5Ј-dAdo, for example by inducing large scale conformational changes such as the TIM barrel motions or by altering active site electrostatics or dynamics to destabilize the C2Ј-endo form or to stabilize the C3Ј-endo form (55,68,69). It is unclear how many molecular mechanisms AdoCbl enzymes use to afford the substantial 10 12 enhancement in Co-C bond homolysis that accompanies substrate binding (1,3,70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the assessment of the steric effect could not be done without using converging freeenergy calculations rather than energy minimization approaches. The important finding that the interactions between the 2′-and 3′-OH groups of the ribose with Glu-370 play a major role is also supported by the reduced activity upon removal of the 2′-OH group (24) and the loss of activity upon mutation of the equivalent Glu-330 in glutamate mutase (25). The above discussion is basically a summary of what we have already established, whereas the focus of the current work is on the origin of the observed entropic effect.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Cobalt can also be substituted for zinc in zinc(II) enzymes to make the still-functioning enzymes spectroscopically active (UV/Vis, magnetic circular dichroism, NMR, and electron paramagnetic resonance spectroscopy). [5][6][7][8] The large number of zinc enzymes provides ample opportunity for these types of substitutions.…”
Section: Introductionmentioning
confidence: 99%